2018
DOI: 10.1002/hyp.13155
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of forest conversion and agriculture practices on water pathways in Southern Brazil

Abstract: Land-use/cover change (LUCC), and more specifically deforestation and multidecadal agriculture, is one of the various controlling factors of water fluxes at the hillslope or catchment scale. We investigated the impact of LUCC on water pathways and stream stormflow generation processes in a subtropical region in southern Brazil. We monitored, sampled and analysed stream water, pore water, subsurface water, and rainwater for dissolved silicon concentration (DSi) and 18 O/ 16 O (δ 18 O) signature to identify cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…Zhou et al () and Krishnaswamy et al () similarly showed major reductions in the storm runoff response after reforesting bare land in South China and overgrazed degraded forest land in India, respectively. The results are also in agreement with previous hydrochemical studies (Chaves et al, ; Robinet et al, ) and runoff plot studies (Chandler & Walter, ) that suggested that overland flow was more widespread in grazed pastures or pasture fallows than in (re)forested sites. In addition to the much higher infiltration rates in the reforested Manobo catchment than the degraded Basper catchment and resulting decreases in overland flow, the soil storage capacity of the Basper grassland has likely been diminished by the continued soil erosion and landsliding (cf.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Zhou et al () and Krishnaswamy et al () similarly showed major reductions in the storm runoff response after reforesting bare land in South China and overgrazed degraded forest land in India, respectively. The results are also in agreement with previous hydrochemical studies (Chaves et al, ; Robinet et al, ) and runoff plot studies (Chandler & Walter, ) that suggested that overland flow was more widespread in grazed pastures or pasture fallows than in (re)forested sites. In addition to the much higher infiltration rates in the reforested Manobo catchment than the degraded Basper catchment and resulting decreases in overland flow, the soil storage capacity of the Basper grassland has likely been diminished by the continued soil erosion and landsliding (cf.…”
Section: Discussionsupporting
confidence: 92%
“…Groundwater levels rose to 30 cm below the surface at the footslope in Manobo, thereby likely activating lateral macropores flow (cf. Noguchi et al, ; Robinet et al, ; Schellekens et al, ). Chandler and Bisogni () found that pipe flow contributed most of the interflow at a forest site on epikarst in the Philippines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the combined effect of geomorphology and land use on soil redistribution and rejuvenation in a subtropical region where the majority of Atlantic rain forest was converted to agricultural land in the 1960s (Minella, 2003;Minella et al, 2008). Our study is part of a larger project on soil systems on global change, where a forested and agricultural catchment in the Guapore river basin in Southern Brazil were studied for short-and long-term soil-landscape dynamics (Ameijeiras-Mariño et al, 2018;Robinet et al, 2018aRobinet et al, , 2018bUnzué-Belmonte et al, 2017;Schoonejans et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of vegetation on the CZ was also examined by Robinet et al (), who explored difference in the structure, hydrology, and geochemistry between natural forests and croplands in subtropical southern Brazil, where agriculture is fast expanding. The authors monitored stream, subsurface, and rain water for dissolved silicon concentration and O and H isotopes, to identify contributing sources to streamflow under forest versus agriculture landcover.…”
Section: How Do Vegetation and Humans Shape The Cz?mentioning
confidence: 99%